Knowledge, practice and understanding of pictograms on medicines informing about prohibition and potential risks of their use during pregnancy. - Vargas-Huillcanina, María (2024)
Background: Pictograms on medications aim to convey essential information, such as potential risks during pregnancy. However, their comprehension varies significantly based on the culture and health practices of each region. Objective: Evaluate the knowledge, practices, and understanding of pictograms warning about potential hazards associated with medication use during pregnancy in pregnant and non-pregnant women attending a reference Maternal Perinatal Institute in Peru. Method: Observational, cross-sectional study with non-random sampling. 409 women were surveyed regarding their knowledge of contraindicated medications during pregnancy, the presence of pictograms, frequency of reviewing package inserts, and interpretation of three U.S. approved pictograms from the Food and Drug Administration and the European Medicines Agency, used in products marketed in Peru. Results: 85% of participants knew about prohibited medications during pregnancy, but only 26.5% were aware of pictograms. Understanding the meaning of the pictograms, indicating "prohibited" or "risky during pregnancy," did not exceed 70%. 40.83% assigned an opposite meaning to the least understood pictogram. Reviewing drug leaflets was associated with higher education (p = 0.02) and having at least one child (p < 0.01). Conclusion: Low knowledge and a lack of understanding of pictograms conveying warnings about medication use during pregnancy highlight the need to improve their clarity on product labels. Further research is required to develop understandable pictograms, especially in culturally diverse settings.